N‐Heterocyclic Carbene Dirhodium(II) Complexes as Catalysts for Allylic and Benzylic Oxidations. Issue 8 (18th February 2013) - Coelho, Jaime A. S.; Trindade, Alexandre F.; Wanke, Riccardo; Rocha, Bruno G. M.; Veiros, Luis F.; Gois, Pedro M. P.; Pombeiro, Armando J. L.; Afonso, Carlos A. M.
Abstract: The experimental conditions (solvent, base, temperature and oxidant) for allylic and benzylic oxidation reactions catalyzed by dirhodium(II)/N‐heterocyclic carbene (NHC) complexes were optimized for the first time in this work. The oxidations of cyclohexene and fluorene were used as model reactions. Two optimized experimental conditions for both types of oxidations were found, which resulted in their ketone [aerobic conditions, 40 °C, 1 equiv. t BuOOH (TBHP)] or tert ‐butyl peroxide derivatives (anaerobic conditions, 25 °C, 2 equiv. TBHP). The dirhodium(II) complexes undergo a single‐electron reversible oxidation by cyclic voltammetry in CH2 Cl2, which is assigned to the Rh2 4+ /Rh2 5+ redox couple at an oxidation potential that is lowered upon sequential axial coordination of further ligands to the Rh–Rh centre. The oxidation potential is discussed in terms of the electron‐donor character of the NHC ligand, which was shown to act as an effective electron‐releaser to the Rh2 4+ centre, and the electrochemical behaviour is compared to the observed catalytic activity. Abstract : An N‐heterocyclic carbene (NHC) ligand at the axial position of Rh2 (carboxylate)4 complexes triggers considerable changes in the electrochemical behaviour of the formed complexes, which also catalyze allylic and benzylic oxidations.